Pengaruh Penggunaan Media Sosial terhadap Konsentrasi Belajar Mahasiswa J-PBSI Universitas Lambung Mangkurat - Nadila Syafa (Inspirasi Dunia: Jurnal Riset Pendidikan dan Bahasa, 2025)
In the context of the influence of social media on the learning concentration of Students in the learning concentration if students in the J-PBSI (Indonesia Language and Literature Education Department) at Lambung Mangkurat University, social media is one of the most influential technological products in the lives of students today. Students in J-PBSI at Lambung Mangkurat University are increasingly dependent on various digital platfroms to support their educational processes. Theses applicantions have become essential tools for socializing and sharing information with other students. The influence of social media use on the learning concentration of J-PBSI students shows that many students experience a lack of focus while studying due to the distracting effects of social media. This distraction often reduces students’ ability to contcentrate, which in turn affects their overall to concentrate, which in turn affects their overall learning performance. This study uses a descriptive qualitative method with in-depth interviem techniques conducted with several students from the Indonesia Language and Literature Education Department. The results of the most students use sosial media on a daily basis. High usage of social media tends to decrease learning concentration because students are often distracted by notifications of the urge to open social media while studying. However, there are also J-PBSI students who use social media effectively, utilizing it as an additional learning resource. Thus, the influence of social media is twofold, depending on the intensity and purpose of ir use. This study aims to determine the extent to which social media affects students’ learning concentration. It is also expected to provide a better understanding of how social media influences the learning process. Students are encouraged to use social media wisely and responsibly so that is does not interfere with their focus on studying, but instead supports their academic activities.